Inflammatory Reaction as Determinant of Foreign Body Reaction Is an Early and Susceptible Event after Mesh Implantation. (25th March 2014) - Gerullis, Holger; Georgas, Evangelos; Borós, Mihaly; Klosterhalfen, Bernd; Eimer, Christoph; Arndt, Christian; Otto, Stephan; Barski, Dimitri; Ysebaert, Dirk; Ramon, Albert; Otto, Thomas
Abstract : Purpose. To investigate and relate the ultrashort-term and long-term courses of determinants for foreign body reaction as biocompatibility predictors for meshes in an animal model. Materials and Methods. Three different meshes (TVT, UltraPro, and PVDF) were implanted in sheep. Native and plasma coated meshes were placed bilaterally: (a) interaperitoneally, (b) as fascia onlay, and (c) as muscle onlay (fascia sublay). At 5 min, 20 min, 60 min, and 120 min meshes were explanted and histochemically investigated for inflammatory infiltrate, macrophage infiltration, vessel formation, myofibroblast invasion, and connective tissue accumulation. The results were related to long-term values over 24 months. Results. Macrophage invasion reached highest extents with up to 60% in short-term and decreased within 24 months to about 30%. Inflammatory infiltrate increased within the first 2 hours, the reached levels and the different extents and ranking among the investigated meshes remained stable during long-term follow up. For myofibroblasts, connective tissue, and CD31+ cells, no activity was detected during the first 120 min. Conclusion. The local inflammatory reaction is an early and susceptible event after mesh implantation. It cannot be influenced by prior plasma coating and does not depend on the localisation of implantation.